Cooperative Learning in Choukai and Tingli Improvement - Anggita Stovia; Rizki Utami; Eko Kurniawan; Hartati Hartati (Journal of Japanese Language Education and Linguistics, 2024)
Previously, instruction in Japanese and Mandarin listening courses (Choukai and Tingli) was conducted through a monotonous learning process. Observations and brief interviews indicated that students typically absorb knowledge from lecturers without engaging in cognitive processes such as translation, comprehension, analysis, or the formulation of analogous examples. This leads to students being passive and even neglecting the learning process. In listening comprehension, although it may seem that the sole activity involves auditory engagement with audio or spoken language other processes are required, particularly for advanced listening courses. In advanced semester courses, students must comprehend more than just the auditory material. The objective of this research is to determine the efficacy of the cooperative learning paradigm in enhancing listening abilities. This study is a quantitative experimental investigation featuring a pre-test prior to treatment and a post-test after treatment. Data gathering methods are conducted through the administration of tests and observations. The cooperative learning strategy implemented in the Choukai and Tingli courses will engage students actively and creatively in analyzing audio and generating additional case studies from diverse perspectives.